Agricultural Product Development for Agricultural Tourism of Ban Khlong Khuean Community, Chachoengsao Province - Srinukoon, Kanchayanis; Maraphot, Kannika (Area Based Development Research Journal, 2021)
Ban Khlong Khuean community, located in Tambon Khlong Khuean, Khlong Khuean district, Chachoengsao province, has various mango species as its community resources. The major types include Nam Dok Mai and Dawei which are sold as fresh mango and processed mango products, namely mango sheets. This research aims to develop agricultural tourism products as well as enhance community dynamics and potential in promoting creative local tourism. This involved operational research work among researchers, community representatives, and network partners.The implementation included 1)the participation process of the networking parties; 2) the development of tourism products and local souvenirs; and 3) the development of human potential.Processed product development includes Nam Dok Mai mango-flavored sweetened condensed milk and mango in light syrup (mango Loikaw) whereas local souvenirs reflecting the community’s identity are t-shirts and cloth bags from Dee Khlong Khuean. The organized training courses, public relations, and expansion of marketing channels result in improved tourism potential. For instance, the community is known to a broader public, attracting external media to film programs for broadcasting, which in return will draw more public interest. The locals can sell products and generate an income of 3,000 - 3,500 baht per month on average. In summary, people in the community have become skilled in local product processing while publicity and distribution channels for community products have been addressed, leading to local development and an increase in community income.